2022
DOI: 10.53730/ijhs.v6ns1.8703
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antibacterial response of hydroalcoholic extract of Plumeria alba leaves

Abstract: Plants are the natural treasure of antioxidants and antimicrobial agents. Present study was intended to evaluate the antioxidant and antimicrobial potential of Plumeria alba leaves hydroalcoholic extract (PALHE). Study involved the phytochemical screening, antioxidant, and antibacterial activity of PALHE. The PALHE was prepared using 95% ethanol as solvent through maceration method. The antioxidant activity involved determination of total phenolic content (TPC) and total flavonoid content (TFC). DPPH (1,1-Diph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Some reports have shown that essential oils possess antioxidant activity, which plays a vital role in neutralizing free radicals and benefiting human health [ 29 , 30 , 33 ]. The antioxidant evaluation of the organic solvent leaf extract of P. alba by Siang and et al revealed moderate antioxidant activity in the DPPH assay, where the IC 50 was found to be 23.96 mg/mL [ 34 ]. Essential oils are therefore better radical scavengers than the organic solvent extracts of the same plant.…”
Section: Resultsmentioning
confidence: 99%
“…Some reports have shown that essential oils possess antioxidant activity, which plays a vital role in neutralizing free radicals and benefiting human health [ 29 , 30 , 33 ]. The antioxidant evaluation of the organic solvent leaf extract of P. alba by Siang and et al revealed moderate antioxidant activity in the DPPH assay, where the IC 50 was found to be 23.96 mg/mL [ 34 ]. Essential oils are therefore better radical scavengers than the organic solvent extracts of the same plant.…”
Section: Resultsmentioning
confidence: 99%